ANTESEDEN DAN KONSEKUEN E-LOYALTY - Prasetya, Adhitya Yoga (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2013)
This paper investigates the antecedents and consequences of customer loyalty in an online business-to-consumer (B2C) context. We identify eight factors (the 8Csâ customization, contact interactivity, care, community, convenience, cultivation, choice, and character) that potentially impact e-loyalty. The paper also reveal that e-loyalty has an impact on two customer-related outcomes: word-of- mouth promotion and willingness to pay more.